Acute endophthalmitis after penetrating and endothelial keratoplasty at a tertiary eye care center over a 13-year period - Shilpa Das; Muralidhar Ramappa; Ashik Mohamed; Sunita Chaurasia; Savitri Sharma; Taraprasad Das (Indian Journal of Ophthalmology, 2020)
Purpose: To evaluate the clinico-microbiological profile, donor cornea risk factors, and outcomes of postkeratoplasty endophthalmitis at a tertiary care center. Methods: Retrospective analysis of charts of 28 consecutive patients (28 eyes) of acute endophthalmitis following either an endothelial keratoplasty (EK) or an optical penetrating keratoplasty (PK) surgery, performed between 2006 and 2018 (13-year period). Positive microbiology, identification and classification of predisposing factors, surveillance of utilized paired donors, treatment outcomes, and differences in the rate and severity of the event between optical penetrating and endothelial keratoplasty. Results: The estimated incidence of endophthalmitis was 0.23% in the entire cohort; it was 0.34% and 0.15%, after EK and PK, respectively (P = 0.049). The median time of endophthalmitis was 4.5 days postsurgery. Donor-related endophthalmitis was recognized in 7/28 (25%) eyes. Culture positivity was 68% (n = 19 of 28). Bacteria was isolated in 84% (n = 16 of 19) instances; Gram-negative bacilli were more common (87.5%; 14 of 16), and Pseudomonas species (50%; 7 of 14) was the most common Gram-negative bacterium. Majority (>75%) of the Gram-negative bacteria were resistant to all fluoroquinolones, aminoglycosides, 3rd generation cephalosporins, and meropenam; 1/3rd were resistant to imipenem; and 90% were sensitive to colistin. Treatment included intraocular antibiotic injections (96.4%), vitrectomy (42.9%), and therapeutic keratoplasty (50%). In 85.7% (24 of 28), globe was salvaged. The final vision was 20/200 or better in 39.1% (9 of 23) eyes. Conclusion: EK carried a higher risk of endophthalmitis than PK in this cohort. Bacterial infection was more common in this series, with Gram negative bacilli being the commonest organisms. Multidrug resistance was common (~75%) in Gram negative isolates.